PENGARUH SISTEM OLAH TANAH DAN APLIKASI HERBISIDA TERHADAP RESPIRASI TANAH PADA PERTANAMAN UBI KAYU (Manihot esculenta Crantz) MUSIM TANAM KE-4 DI GEDONG MENENG - Nur Afni Afrianti; Ainin Niswati; Arif Wicaksono; Henrie Buchari (STIPER Dharma Wacana Metro, 2019)
Soil respiration is the process of releasing CO2 from the soil into the atmosphere, mainly produced by soil microorganisms and plant roots. Soil respiration is influenced by biological factors (vegetation, microorganisms), environmental factors (temperature, humidity, pH) and also human factors (tillage and herbicides). This research aims to determine: (1) the effect of soil treatment systems on soil respiration in cassava cultivation; (2) the effect of herbicide application on soil respiration in cassava cultivation; (3) the effect of interaction between tillage systems and application of herbicides on soil respiration in cassava cultivation. The treatment was designed as a factorial in Randomized Block Design with 2 factors and 4 replications. The first factor is the soil tillage system (Minimum Tillage, Intensive Tillage) and the second factor is the application of herbicides (non-herbicides, herbicide applications). The results showed that the tillage system and herbicide application had no significant effect on soil respiration and there was no interaction between the tillage system and herbicide application on cassava (Manihot esculenta Crantz.). Soil respiration at 3 months after planting is higher than 6 and 11 months after planting. Soil water content are higher in non-herbicide application at 11 months after planting. Soil temperature is significantly correlated with soil respiration at 3 months after planting. Soil water content, soil temperature and soil C-organic did not affect soil respiration.